Monitoring environmental impacts of fish farms: Comparing reference conditions of sediment geochemistry and benthic foraminifera with the present. (January 2021) - Klootwijk, Anouk T.; Alve, Elisabeth; Hess, Silvia; Renaud, Paul E.; Sørlie, Carsten; Dolven, Jane K.
Highlights: Modern stratigraphic records successfully establish reference conditions. Surrounding bedrock introduces naturally high concentrations of Ni. Geochemical parameters and benthic foraminiferal indices showed no fish farm impact. Benthic foraminifera are relevant to implement in environmental monitoring systems. Macrofauna and living foraminifera seem to respond in a similar fashion. Abstract: Intensive fish farming is a major industry, but the extent of organic matter (OM) and heavy metal pollution by fish farms is debated. This study established in situ reference conditions using geochemical parameters and fossil benthic foraminiferal assemblages in dated sediment cores to identify potential impacts of fish farming in two basins of the inner Øksfjord, Northern Norway. Living (rose Bengal stained) benthic foraminifera were used to assess the present day environmental conditions. The fossil foraminiferal records were compared with the living foraminifera, which in turn were compared with macrofaunal data. Long-term (>100 yrs) sediment core records of the geochemical parameters (TOC63, C/N, δ 13 CVPDB TOC and heavy metals) and foraminiferal indices (Norwegian Quality Index (fNQI), AZTI's Marine Biotic Index (fAMBI), fHlog2, ES100 ) did not indicate an impact from fish farming through time. Long-term changes in foraminiferal absolute abundances and relative abundances of ecological groups (EGs) reflecting organic matter (OM) tolerance suggest that the OM supply slightly increased compared to reference conditions. Relative abundances of Brizalina skagerrakensis and Epistominella vitrea, previously associated with phytodetrital input, suggest a minor increase in primary productivity compared to reference conditions. The Stainforthia group ( S. fusiformis and S. feylingi ), indicative of OM enrichment, in the living foraminiferal assemblages may indicate a response to fish farming activities, but foraminiferal seasonality could not be excluded as a potential cause. The indices of both fossil and living foraminifera, in addition to the macrofauna showed a good to high Ecological Quality Status (EcoQS) through time and at present. This indicates that environmental conditions have been and still are acceptable.